Seismic Microzoning as a Basis for "Lowering" Seismic Risk Analysis at the Level of Local Self Government (International Journal of Contemporary Security Studies, 2023)
In most cases, seismic hazard and seismic risk analyzes are performed by national institutions in the Republic of Serbia, while seismic micro-zoning is in most cases neglected, although it is an important element in these analyzes. The paper will deal with the problems in the division of competencies and jobs in this area, as well as the importance of the work itself, which results in the resilience of infrastructure and society in general when it comes to natural disasters.The paper presents different types-levels of seismic micro-zoning and explains the benefits of their application in the planning and design of buildings and infrastructure, and above all "lowering" the assessment of seismic and geological risk to the level of local government. The importance of conducting field research geological and geophysical works was emphasized, both for the needs of more precise seismic risk analysis at a specific micro location, and from the aspect of geological risks that must be taken into account when conducting detailed seismic microzoningThrough concrete examples, all the effects that end users such as cities, municipalities and individual users can have from seismic micro-zoning are explained. Also, it is shown how new technologies can help to map hazards and risks, share data and all in favor of multi-hazard approaches in defining and assessing risks as well as in further application of preventive measures.